2022
DOI: 10.1111/obr.13429
|View full text |Cite
|
Sign up to set email alerts
|

The role of the androgen receptor in the pathogenesis of obesity and its utility as a target for obesity treatments

Abstract: Summary Obesity is associated with hypothalamic–pituitary–testicular axis dysregulation in males. Here, we summarize recent evidence derived from clinical trials and studies in preclinical animal models regarding the role of androgen receptor (AR) signaling in the pathophysiology of males with obesity. We also discuss therapeutic strategies targeting the AR for the treatment of obesity and their limitations and provide insight into the future research necessary to advance this field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 353 publications
(467 reference statements)
1
11
0
Order By: Relevance
“…GO term and pathway enrichment analysis showed that DEGs were highly enriched in the present investigation, which undoubtedly verifies the reliability of our results. Signaling pathways include cytokine signaling in immune system [ [87], CES1 [88], CYP19A1 [89], PLAC8 [90], CD36 [91], GIPR (gastric inhibitory polypeptide receptor) [92], ARG1 [93], MSR1 [94], DOCK2 [95], S1PR1 [96], OXTR (oxytocin receptor) [97], F11R [98], LEPR (leptin receptor) [99], AR (androgen receptor) [100], DKK3 [101], FOXO1 [102], PIK3CB [103], WWP1 [104], PHIP (pleckstrin homology domain interacting protein) [105], MPZL3 [106], FBXO2 [107], GUCY2C [108], ADRA2A [109], CHRNA5 [110], GLP2R [111], SDC3 [112], NFAT5 [113], PON2 [114], PRNP (prion protein) [115], DGKE (diacylglycerol kinase epsilon) [116], ARHGAP21 [117], COQ2 [118], EPHX2 [119] and FAM3C [120] were observed to be associated with the progression of obesity. Vargas-Alarcón et al [121], Frantz et al [122], Bosè et al [123], Gu et al [124], Liu et al [125], Szirák et al [126], Ye et al [127], Alikhah et al [128], Chen et al [129], Mao et al…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…GO term and pathway enrichment analysis showed that DEGs were highly enriched in the present investigation, which undoubtedly verifies the reliability of our results. Signaling pathways include cytokine signaling in immune system [ [87], CES1 [88], CYP19A1 [89], PLAC8 [90], CD36 [91], GIPR (gastric inhibitory polypeptide receptor) [92], ARG1 [93], MSR1 [94], DOCK2 [95], S1PR1 [96], OXTR (oxytocin receptor) [97], F11R [98], LEPR (leptin receptor) [99], AR (androgen receptor) [100], DKK3 [101], FOXO1 [102], PIK3CB [103], WWP1 [104], PHIP (pleckstrin homology domain interacting protein) [105], MPZL3 [106], FBXO2 [107], GUCY2C [108], ADRA2A [109], CHRNA5 [110], GLP2R [111], SDC3 [112], NFAT5 [113], PON2 [114], PRNP (prion protein) [115], DGKE (diacylglycerol kinase epsilon) [116], ARHGAP21 [117], COQ2 [118], EPHX2 [119] and FAM3C [120] were observed to be associated with the progression of obesity. Vargas-Alarcón et al [121], Frantz et al [122], Bosè et al [123], Gu et al [124], Liu et al [125], Szirák et al [126], Ye et al [127], Alikhah et al [128], Chen et al [129], Mao et al…”
Section: Discussionmentioning
confidence: 99%
“…Signaling pathways include cytokine signaling in immune system [48], extracellular matrix organization [49], diseases of metabolism [50], hemostasis [51], innate immune system [52], metabolism of lipids [53] and metabolism [54] were linked with progression of PCOS. Altered expression of PLA2G5 [55], CASP1 [56], EDNRA (endothelin receptor type A) [57], F2RL1 [58], FOXP3 [59], DRD4 [60], COL6A3 [61], TIMP4 [62], SOCS1 [63], CD74 [64], TGFB1 [65], ATF5 [66], IRF7 [67], IRX3 [68], FOXC2 [69], STX1A [70], IL1RL1 [71], HHIP (hedgehog interacting protein) [72], ELOVL2 [73], BGN (biglycan) [74], POMC (proopiomelanocortin) [75], DOK5 [76], COL1A1 [77], POSTN (periostin) [78], SOD3 [79], ZNF423 [80], FABP5 [81], DDIT4 [82], KCTD15 [83], COL1A2 [84], MGAT2 [85], ENDOG (endonuclease G) [86], HSPA5 [87], CES1 [88], CYP19A1 [89], PLAC8 [90], CD36 [91], GIPR (gastric inhibitory polypeptide receptor) [92], ARG1 [93], MSR1 [94], DOCK2 [95], S1PR1 [96], OXTR (oxytocin receptor) [97], F11R [98], LEPR (leptin receptor) [99], AR (androgen receptor) [100], DKK3 [101], FOXO1 [102], PIK3CB [103], WWP1 [104], PHIP (pleckstrin homology domain interacting protein) [105], MPZL3 [106], FBXO2 [107], GUCY2C [108], ADRA2A [109], CHRNA5 [110], GLP2R [111], SDC3 [112], NFAT5 [113], PON2 [114], PRNP (prion protein) [115], DGKE (diacylglycerol kinase epsilon) [116], ARHGAP21 [117], COQ2 [118], EPHX2 [119] and FAM3C […”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The AR is known to affect the lipid cascade at multiple levels. 2 , 3 Till date, some studies have shown the role of AR in regulating the expression of cellular genes and proteins. Previously, in a study on multiple sclerosis, AR was observed to adversely regulate transcription factors of members of the Transforming growth factor TGFF-β/SMAD pathway.…”
Section: Introductionmentioning
confidence: 99%